The devil's novice - Peters, Ellis, 1913-1995 (Peters, Ellis, 1913-1995. Chronicles of Brother Cadfael, 1997)
The year is 1140. Suspicions abound when a young man turns up at Shrewsbury Abbey wanting to join as a novice and the half-burnt body of a missing cleric is found.